Effect of Hydrodynamic Forces on meso‐(4‐Sulfonatophenyl)‐Substituted Porphyrin J‐Aggregate Nanoparticles: Elasticity, Plasticity and Breaking. Issue 28 (30th May 2016) - El‐Hachemi, Zoubir; Balaban, Teodor Silviu; Campos, J. Lourdes; Cespedes, Sergio; Crusats, Joaquim; Escudero, Carlos; Kamma‐Lorger, Christina S.; Llorens, Joan; Malfois, Marc; Mitchell, Geoffrey R.; Tojeira, Ana P.; Ribó, Josep M.
Abstract: The J aggregates of 4‐sulfonatophenyl meso ‐substituted porphyrins are non‐covalent polymers obtained by self‐assembly that form nanoparticles of different morphologies. In the case of high aspect‐ratio nanoparticles (bilayered ribbons and monolayered nanotubes), shear hydrodynamic forces may modify their shape and size, as observed by peak force microscopy, transmission electron microscopy of frozen solutions, small‐angle X‐ray scattering measurements in a disk‐plate rotational cell, and cone–plate rotational viscometry. These nanoparticles either show elastic or plastic behaviour: there is plasticity in the ribbons obtained upon nanotube collapse on solid/air interfaces and in viscous concentrated nanotube solutions, whereas elasticity occurs in the case of dilute nanotube solutions. Sonication and strong shear hydrodynamic forces lead to the breaking of the monolayered nanotubes into small particles, which then associate into large colloidal particles. Abstract : Forced into shape : Nanotubes of J aggregates may collapse to form plastic bilayered ribbons when deposited on surfaces, and may break upon sonication or vortexing into smaller nanoparticles, which then tend to aggregate into large colloidal particles (see figure).